Nuclear-Order-Induced Quantum Criticality and Heavy-Fermion Superconductivity at Ultra-low Temperatures in YbRh2Si2 - Schuberth, Erwin; Wirth, Steffen; Steglich, Frank (Frontiers in Electronic Materials, 2022)
The tetragonal heavy-fermion metal YbRh2Si2 orders antiferromagnetically at T_N = 70 mK and exhibits an unconventional quantum critical point (QCP) of Kondo-destroying type at B_N = 60 mT, for the magnetic field applied within the basal (a,b) plane. Ultra-low-temperature magnetization and heat-capacity measurements at very low fields indicate that the 4f-electronic antiferromagnetic (AF) order is strongly suppressed by a nuclear-dominated hybrid order (‘A-phase’) at T_A <= 2.3 mK, such that a QCP becomes established at B 0 (Schuberth et al., 2016). This enables the onset of heavy-fermion superconductivity (T_c = 2 mK) which appears to be suppressed by the primary AF order at elevated temperatures. Measurements of the Meissner effect reveal bulk superconductivity, with T_c decreasing under applied field to T_c < 1 mK at B > 20 mT. The observation of a weak but distinct superconducting shielding signal at a temperature as high as 10 mK suggests the formation of insulated random islands with emergent A-phase order and superconductivity. Upon cooling, the shielding signal increases almost linearly in temperature, indicating a growth of the islands which eventually percolate at T 6.5 mK, as inferred from recent electrical-resistivity results by Nguyen et al., (2021). These authors also report on two superconducting regions, the first one below 4 mT, with the highest T_c occurring at B = 0, and a second ‘dome-shaped’ regime with much lower T_c at 4 mT < B < 60 mT.